2016
DOI: 10.1093/jxb/erw165
|View full text |Cite
|
Sign up to set email alerts
|

Life without complex I: proteome analyses of an Arabidopsis mutant lacking the mitochondrial NADH dehydrogenase complex

Abstract: HighlightComplex I dysfunction causes reorganization of cellular respiration and affects metabolic processes in mitochondria, plastids, peroxisomes, and other cellular compartments with drastic consequences for growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 81 publications
4
71
0
Order By: Relevance
“…Their presence has implications for the physiological role of complex I. However, even in plants, complex I is an essential site for electron flow into the ETC under most physiological conditions, as deletion of complex I genes causes a drastic delay in plant development and loss of plant fertility (Fromm et al ).…”
Section: Mitochondrial Complex I From Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their presence has implications for the physiological role of complex I. However, even in plants, complex I is an essential site for electron flow into the ETC under most physiological conditions, as deletion of complex I genes causes a drastic delay in plant development and loss of plant fertility (Fromm et al ).…”
Section: Mitochondrial Complex I From Plantsmentioning
confidence: 99%
“…Simultaneous deletion of two of the genes encoding CA/CAL proteins caused strong developmental problems at the seed stage (CAL1 + CAL2 deletion or CA1 + CA2 deletion), except if one of the two deleted genes encoded CA3 (e.g. CA1 + CA3 deletion) (Wang et al , Córdoba et al , Fromm et al , ). Seeds from CA1/CA2 double‐mutant could be rescued by cultivation on sucrose; plants could be regenerated, but were strongly delayed in development (Fromm et al ).…”
Section: Mitochondrial Complex I From Plantsmentioning
confidence: 99%
“…The γca1γca2 mutants lack Complex I altogether, and do not produce viable seed, having to be maintained using an embryo rescue method, which involves supplying the embryos with sucrose in the growth medium (Fromm et al., 2016a, Fromm et al., 2016b). The double mutants also exhibit high levels of Complexes II and IV (succinate dehydrogenase and cytochrome oxidase, respectively), and the alternative oxidase, and in contrast, reduced levels of photosynthetic proteins (Fromm et al., 2016c). …”
Section: Plant γ Carbonic Anhydrasesmentioning
confidence: 99%
“…In contrast, Complex I is responsible for oxidation of NADH produced during respiration and it is the main point of entry of electrons into the mitochondrial electron transfer chain, providing up to 40% of the protons for the formation of ATP (Fromm et al ). Unlike its chloroplast counterpart, lack of this complex affects carbon metabolism and photosynthesis (Fromm et al ), and entails profound changes leading to curled leaves and delayed reproductive and vegetative development phenotype (de Longevialle et al ). Surprisingly, recent studies have found that hemiparasitic mistletoe has lost the ability to produce a functional Complex I (da Fonseca‐Pereira et al ) pointing to more similarities to the NDH complex.…”
Section: Nadh Dehydrogenase: the Main Target?mentioning
confidence: 99%